2012
DOI: 10.1159/000342708
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Complementary and Alternative Medicine Prevalence in EU

Abstract: Background: Studies suggest that complementary and alternative medicine (CAM) is widely used in the European Union (EU). We systematically reviewed data, reporting research quality and the prevalence of CAM use by citizens in Europe; what it is used for, and why. Methods: We searched for general population surveys of CAM use by using Ovid MEDLINE (1948 to September 2010), Cochrane Library (1989 to September 2010), CINAHL (1989 to September 2010), EMBASE (1980 to September 2010), PsychINFO including PsychARTICL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
190
2
23

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(228 citation statements)
references
References 98 publications
(53 reference statements)
13
190
2
23
Order By: Relevance
“…Oral administration of herbals in females may be most common in the population. Such observation is often made in CAM/herbal use prevalence studies [1][2][3]. It is therefore expected that this population is also overrepresented in all included reports.…”
Section: Suspect Herbalsmentioning
confidence: 92%
See 1 more Smart Citation
“…Oral administration of herbals in females may be most common in the population. Such observation is often made in CAM/herbal use prevalence studies [1][2][3]. It is therefore expected that this population is also overrepresented in all included reports.…”
Section: Suspect Herbalsmentioning
confidence: 92%
“…There is an increased prevalence in use of herbal medicines among the adult population in many western countries [1][2][3]. The most recent 2012 US National Health Interview Survey showed that 18% of adults used natural products including herbal medicine during the past 12 months [3].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the project yielded recommendations for the European Commission and the European Parliament. European studies of the prevalence of CAM tend to be poor and heterogeneous (43) and also tend to display huge variability in the national regulatory management which makes a comparison across the EU nearly impossible (44). Some of the research published looks at the determinants of the use of CAM in countries like Finland (45), Italy (46,47), Germany (48), Sweden (49,50) and the UK (51).…”
Section: Implications For Policy Makersmentioning
confidence: 99%
“…Acupuncture is gaining popularity as a non-pharmacological option in pain medicine [1,2]. There is substantial evidence for acupuncture being effective in the treatment of acute [3][4][5] and chronic pain [6].…”
Section: Introductionmentioning
confidence: 99%